The Effect of Profitability, Liquidity, and Company Size on Company Value in The Banking Subsector - Ni Kadek Sanex Indrawati Cahyani; Ni Luh Putu Sri Purnama Pradnyani; Rai Gina Artaningrum (International Journal of Pertapsi, 2023)
This study examines the effect of profitability, liquidity, and firm size on firm value. Quantitative research in this study with secondary data in the form of financial statements and annual reports of banking sub-sector companies listed on the IDX from 2019 to 2021. The sample determination method used purposive sampling with the following criteria: 1) banking subsector companies listed on the IDX during the study period, 2) banking subsector companies that presented consistent and complete financial statements and annual reports during the study period, 3) banking subsector companies that did not experience or suffer losses during the research period from 2019-2021, so as to obtain data of 45 observations. The data analysis approach used in this study is multiple linear regression analysis, with the assistance of SPSS 20 for data display. The present study involves the examination of data via the use of the SPSS analysis tool, namely version 20, in order to conduct an analysis of multiple linear regression. The findings of this research suggest that the relevance of profitability positively impacts the valuation of a corporation. The presence of liquidity has a favorable impact on the valuation of firms. The size of a corporation has a favorable impact on its worth. The findings indicate that the value of the business is influenced by three key criteria, namely profitability, liquidity and firm size. Investors are likely to take this element into account when making investment decisions, since a rise in the value of a firm is often accompanied by an increase in its stock price, so as to guarantee that investors may get maximum returns on their investments.